2021
DOI: 10.1088/1361-6439/ac0a58
|View full text |Cite
|
Sign up to set email alerts
|

Research on dynamics of bouncing ball in triboelectric nanogenerator

Abstract: Bouncing ball based Triboelectric Nanogenerator (BB-TENG) can be used to harvest vibrational energy and sense signal for self-powered sensor in the non-resonant zone because of its non-spring vibration system. The energy harvesting efficiency and sensing effectiveness are significantly affected by the dynamics of the bouncing ball. However, due to the chaotic and nonlinear mechanics, the dynamics of the bouncing ball inside BB-TENG and the corresponding influencing factors have not yet been revealed, which res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 36 publications
0
1
0
Order By: Relevance
“…The excellent performance of HSI-TENG makes it have great potential in mechanical monitoring and provides a novel strategy for self-powered machinery monitoring. Similarly, Du et al also demonstrated the bouncing-ball triboelectric sensor (BB-TENG) with a high signal-to-noise ratio of 34.5 dB at the vibration frequency of 10 Hz to 50 Hz by using the same structure of single ball forced vibration [85,148].…”
Section: Curved Surface Contact Vibration Sensormentioning
confidence: 95%
See 2 more Smart Citations
“…The excellent performance of HSI-TENG makes it have great potential in mechanical monitoring and provides a novel strategy for self-powered machinery monitoring. Similarly, Du et al also demonstrated the bouncing-ball triboelectric sensor (BB-TENG) with a high signal-to-noise ratio of 34.5 dB at the vibration frequency of 10 Hz to 50 Hz by using the same structure of single ball forced vibration [85,148].…”
Section: Curved Surface Contact Vibration Sensormentioning
confidence: 95%
“…As a new research field, TENGs have achieved remarkable results in the application scenario of ship and ocean engineering [30,[79][80][81][82][83]. It is used to convert marine mechanical vibration into reliable and obvious electrical signals to characterize the working condition of marine equipment or marine environmental parameters, which lays the foundation for the development of intelligent marine sensor network [84][85][86][87][88][89]. Some teams have been engaged in related research and have achieved some results.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In particular, scientists have put great efforts into designing novel pressure/strain sensors. According to their sensing mechanisms, these advanced pressure/strain sensors can be classified as resistive [4,19,20], capacitive [4,18,21,22], triboelectric [9,23,24], and piezoelectric [25] modes [26]. The capacitive pressure/strain sensors, consisting of two soft electrodes sandwiching a flexible dielectric layer, possess high sensitivity, low detective range, and simple fabrication process [7,27].…”
Section: Introductionmentioning
confidence: 99%